Colletotrichum Spp. Diversity Between Leaf Anthracnose and Crown Rot From the Same Strawberry Plant - Hu, Shuodan; Zhang, Yanting; Yu, Hong; Zhou, Jiayan; Hu, Meihua; Liu, Aichun; Wu, Jianyan; Wang, Hancheng; Zhang, Chuanqing (Frontiers in Microbiology, 2022)
Leaf anthracnose (LA) and anthracnose crown rot (ACR) represent serious fungal diseases that pose significant threats to strawberry production. To characterize the pathogen diversity associated with above diseases, 100 strawberry plants, including varieties of ‘Hongjia’, ‘Zhangji’, and ‘Tianxianzui,’ were sampled from Jiande and Zhoushan, the primary plantation regions of Zhejiang province, China. A total of 309 Colletotrichum isolates were isolated from crown (150 isolates) and leaves (159 isolates) of affected samples. Among these, 100 isolates obtained from the plants showing both LA and CR symptoms were selected randomly for further characterization. Based on the morphological observations combined with phylogenetic analysis of multiple genes (ACT, ITS, CAL, GAPDH, CHS), all the 100 tested isolates were identified as C. gloeosporioides species complex, including 91 isolates of C. siamense, 8 isolates of C. fructicola causing both LA and CR, and one isolate of C. aenigma causing CR. The phenotypic characteristics of these isolated species were investigated using the BIOLOG phenotype MicroArray (PM) and a total of 950 different metabolic phenotype were tested, showing the characteristics among these isolates and providing the theoretical basis for pathogenic biochemistry and metabolism. The pathogenicity tests showed that even the same Colletotrichum species isolated from different diseased tissues (leaves or crowns) had significantly different pathogenicity towards strawberry leaves and crown. C. siamense isolated from diseased leaves (CSLA) was more aggressive than C. siamense isolated from rotted crown (CSCR) during the infection on ‘Zhangji’ leaves. Additionally, C. fructicola isolated from affected leaf (CFLA) caused more severe symptoms on the leaves of four strawberry varieties compared to C. fructicola isolated from diseased crown (CFCR). For crown rot, the pathogenicity of CSCR was higher than that of CSLA.